2017
DOI: 10.1016/j.molstruc.2017.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation, spectroscopic and energy level studies of Schiff base: 2-[(3′- N -salicylidenephenyl)benzimidazole] using experimental and DFT methods

Abstract: The Schiff base 2-[(3′-N-salicylidenephenyl)benzimidazole] (Spbzl) was characterized by FT-Raman, 1 H NMR, 13 C NMR and single crystal X-ray diffraction technique. Crystallographic studies reveal the presence of two water molecules in the asymmetry unit which aid the intermolecular hydrogen bonding with imidazole ring, and the trans-conformation of the azomethine bond. Theoretical computations conducted using density functional theory (DFT) analysis support the experimental facts. Energy levels estimated by DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…1 H NMR spectra show the characteristic signals of the different systems present in these Schiff bases [ 34 , 35 , 36 ]. At a low field, the signals corresponding to the protons of the imidazole and the -OH present in the salicylidene ring were observed.…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR spectra show the characteristic signals of the different systems present in these Schiff bases [ 34 , 35 , 36 ]. At a low field, the signals corresponding to the protons of the imidazole and the -OH present in the salicylidene ring were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The infrared spectra were obtained using a Shimadzu Affinity 1 (FT-IR) spectrometer. 1 H and 13 C{ 1 H} NMR spectra of the benzimidazolyl-phenol ligands and its lanthanide complexes were recorded on the Bruker Avance II 400 spectrometer using DMSO-d 6 as a solvent. The thermal analysis was performed on the TGA 550 TA Instruments analyzer under nitrogen atmosphere between 50 and 500 C, with a heating rate of 10 C⋅min À1 .…”
Section: Methodsmentioning
confidence: 99%
“…Benzimidazoles are a class of bioactive heterocyclic compounds that display a wide range of useful biological and clinical applications [1]. The benzimidazole backbone represents a privileged structure in medicinal chemistry due to its broad spectrum of pharmacological and therapeutic applications, which include, antimicrobial, antiviral, antiparasitic, anti-inflammatory, antidiabetic and anticancer activities, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The solid was filtered, dried and recrystallized in methanol. The X-ray crystallographic studies of the ligand is reported elsewhere [30]. m.p.…”
Section: Methodsmentioning
confidence: 99%